IJCM_301A: Perceived stigma and quality of life in patients living with HIV/AIDS attending antiretroviral therapy centre in a tertiary care hospital in Jammu. - Zaffer Imran; Kumari Rashmi; Gupta Rajiv K (Wolters Kluwer Medknow Publications, 2024)
Background: HIV/AIDS remains a significant global health challenge, affecting the well-being of millions around the world. While HIV treatments have demonstrated effectiveness, ongoing research indicates the persistence of various psychosocial challenges that tend to compromise the quality of life for individuals coping with HIV/AIDS. Notably, stigma associated with HIV/ AIDS remains widespread among affected individuals, exerting detrimental impacts on their overall quality of life Objective: To assess the quality of life in patients living with HIV/AIDS and to assess the relationship between perceived stigma and quality of life in patients living with HIV/AIDS attending an antiretroviral therapy centre in a tertiary care hospital in Jammu Methodology: This observational cross-sectional study was conducted among patients with HIV/AIDS over a period of 8 months who were attending an antiretroviral therapy centre in a tertiary care hospital of Jammu city of UT of J&K, using systematic random sampling. Patients were administered a questionnaire comprising socio-demographic data, (Pozqol scale) for quality of life and a short version (HSS-12) of the Berger HIV Stigma Scale. Data was analyzed using SPSS version 23.0 software Results: A total of 300 patients were included in the study. The mean age of patients was 42.13±10.48. Mean scores for psychological, social, health and functional domains of quality of life were 10.79Â±3.76, 10.18±3.70, 8.81±3.16 and 10.76±3.35 respectively. Overall quality of life was found to be significantly associated with marital status and HIV status of spouse/partner. There were significant negative correlations between various dimensions of stigma and different domains of quality of life Conclusion: Our findings indicated that higher HIV/AIDS-related perceived stigma decreases the quality of life in patients living with HIV/AIDS. "Prioritizing efforts to reduce stigma, enhance healthcare plans, and improve economic conditions is crucial for fostering improvements in the overall quality of life and its associated domains in the lives of patients living with HIV/AIDS."